Google Clasroom: Upaya Meningkatkan Hasil Belajar Sosiologi Pada Siswa SMA - Warsun, Warsun (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2022)
The research method used is classroom action research. Based on data analysis, it was obtained an average of 77.22 high from the number of 25 students, with the distribution of categories with high learning motivation of 10 students; in the category of moderate learning motivation of Sociology 15 students; while the Low 0; and a total of 25 students. The result of this study is the increase in student learning outcomes in learning Sociology. This can be seen from the increase in the percentage of student learning outcomes from before the action, cycle I to cycle II. In the pre-cycle the number of 25 students who reached the KKM was 7 students, 28%, in the first cycle it became 64.00% or 16 students. In the second cycle the number of students who reached the KKM increased to 100% or 25 students. Thus it can be concluded that the use of the Google Classroom application can improve learning outcomes in Sociology subjects.